(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
How can we understand the common experience of unreflectively adopting what feels like ’different personalities’ in the company of different people? Orthodox theories of personality have not really engaged with this experience, beyond the debate about situation-specificity of behaviour forty years ago. In this article the work of George Mead and Maurice Merleau-Ponty is drawn on to elaborate the concept of joint action. Following Rosenthal and Bourgeois (1991), the common ground between these two theorists is explored.